Connected leadership: Jeremiah 8:18-9:3 – a case study - Wessels, W. J. (Koers, 2010)
The purpose of this article is to address the matter of connected leadership. The point of departure is a biblical passage from Jeremiah 8:18-9:3. The focus of this article is confined to the aspect of connectedness and related issues. The argument put forward is that the rhetorical nature of texts has the ability to engage many readers over time and generations. Not only did the poetic nature of Jeremiah 8:18-9:3 convey the words once spoken by a prophet, but the rhetoric also conveyed the passion of the prophet and of Yahweh for the wounded and broken people of Judah. Added to that is the fact that within the Christian tradition the belief is that the text will find meaning in new contexts as well. Jeremiah 8:18-9:3 brings to the table an element that leaders – especially religious and Christian leaders – need to take note of. Leaders should answer to a “higher power” and to ethical norms because of connectedness to this ‘‘higher power”. As a leader, Jeremiah identified with his people and their woeful condition. But because of his connectedness to Yahweh, he was willing to confront them and point out their wrongdoings. He was not prepared to sacrifice his beliefs and convictions for the sake of popularity.